Growth performance of three genotypes of ducks in coastal region of Bangladesh (Bangladesh Journal of Animal Science, 2012)
A study was conducted to determine the growth performance and mortality rate of Khaki Campell, Jinding and Deshi genotypes in two coastal locations of Barisal and Bhola districts of Bangladesh. Sixty-day-old ducks of 3 genotypes were randomly allocated to 3 treatments having 4 replications in each. Ducks are reared up to 150 days and at the end of experiment one male Khaki Campbell of highest live weight was selected from each replicate group. The average weekly body weight gain (g/bird) of the Khaki Campbell and Jinding were significantly (p